Cutaneous collagenous vasculopathy: A rare case report - Kinjal Deepak Rambhia; Snehal D Hadawale; Uday S Khopkar (Wolters Kluwer Medknow Publications, 2016)
Cutaneous collagenous vasculopathy (CCV) is a distinct, rare, and underdiagnosed condition. We report a case of CCV in a 50-year-old woman presenting as asymptomatic, erythematous to hyperpigmented nonblanchable macules over both the lower extremities. The clinical differential diagnosis of the lesions was pigmented purpuric dermatoses (Schamberg's purpura) and cutaneous small vessel vasculitis. Histology of the lesions revealed dilated superficial dermal vessels with abundant pink hyaline material in the vessel wall, which stained with periodic acid Schiff stain. The patient was diagnosed as CCV. This condition remains largely underdiagnosed and is commonly mistaken for pigmented purpuric dermatosis or generalized essential telangiectasia. Emphasis on the differentiation of CCV from its clinical and histological mimicks is made.